Russian language and corpus diversity РУССКИЙ ЯЗЫК И КОРПУСНОЕ РАЗНООБРАЗИЕ - Piperski, Aleksandr (2020 Annual International Conference on Computational Linguistics and Intellectual Technologies, Dialogue 2020, 2020)
This paper discusses the use of most widely-known Russian corpora, namely Russian National Corpus, ruTenTen, General Internet Corpus of Russian, and Araneum Russicum Maximum, for the theoretical study of Russian language. Based on a sample of papers from 2019, I demonstrate that scholars, especially theoretical linguists, tend to ignore the opportunities provided by a wide range of Web corpora, even though these resources are well-known to the NLP community. I present a selection of case studies to show that data from “non-classical” corpora can be used for studying various linguistic phenomena, such as: 1) variation in morphology and syntax; 2) word formation and lexical change; 3) construction grammar. I also claim that the underuse of non-classical corpora is partly due to the fact that they are (perceived as) not quite user-friendl
Keywords: Corpus linguistics; Russian; Methodology of corpus-based studies; Web as corpus